Priporočila za nekemično zatiranje pelinolistne ambrozije : Ambrosia artemisiifolia L. - Paušič, Andrej; Lešnik, Mario (University of Maribor Press, 2021)
Recommendations for Non-chemical Control of Common Ragweed: Ambrosia artemisiifolia L.The monograph, entitled Recommendations for non-chemical control of common ragweed: Ambrosia artemisiifolia L. holistically describes the up-to date techniques for control of allochthonous, invasive plant species, on the example of common ragweed. The most important mechanical methods and techniques of common ragweed control, the effects of the methods themselves, as well as a comparison between the individual technique of species control are represented and described in this book. A special chapter is devoted to the economics of weed control in the urban environments, using brushing methods, the use of fire, steam and biotic methods of common ragweed control. These modern approaches of the control of allochthonous weed taxa are nowadays indeed relevant, due to the abolition of the use of many herbicides in public areas. The monograph was prepared to educate agricultural advisers, farmers, ecologists, as well as a wider circle of readers.